Production of Carbon Nanotube - Shagufta Parveen M.A. (International Journal of Advanced Science and Technology, 2020)
Carbon nanotubes after their discovery in 1991 have become most important material for future applications. They have remarkable mechanical, chemical, thermal, optical, electrical properties hence attracting many researchers and industries. This paper describes methods of synthesis of carbon nanotubes namely arc discharge, Laser ablation and chemical vapor deposition (CVD).Here CVD is proposed as best method for production of carbon nanotubes from industrial point of view as it is relatively simple, energy efficient, inexpensive and gives large scale production of CNTs. Keywords: arc discharge, CNTs, CVD, laser ablation